Pemanfaatan Sistem Informasi Geografis untuk Pemantauan Karies di Wilayah Kerja Puskesmas Ambulu Kabupaten Jember - Nadhirah Anindita Raniah Yunita; Surartono Dwiatmoko; Hestieyonini Hadnyanawati (Fakultas Kedokteran Gigi Universitas Jember, 2020)
In line with the development of science and technology, and increasing human needs to make things easier, a technology called Geographic Information System (GIS) was created. Geographical information system (GIS) is a technology which is currently a very essential tool in the process of storing, manipulating, analyzing, and displaying natural conditions (including the utility network) with the help of attribute and spatial data (graphic). Based on the data from the visit reports of Dental Clinic in Ambulu Community Health Center from SP2TP section, the grouping of patients with dental caries is only based on the age of the patient and the working area that has village maternity home and auxiliary health center, so that the available information cannot represent all of the working area. Information on areas with the highest caries population can be the attention of the head of the dental clinic of Ambulu Community Health Center to conduct a promotive and preventive service program in the area. This study aimed to determine the use of geographic information systems for caries monitoring in the working area of Ambulu Community Health Center, Jember Regency. This research uses qualitative research. Based on the research that has been done, it can be concluded that the monitoring of caries in the working area of the Ambulu Community Health Center can be done by utilizing a geographic information system, so that the number of patients who have caries in each region can be known. This information can be used by dentists to plan promotive and preventive service activities that will be carried out.